Competitive Differentiation Strategy of EV Battery Products of Vietnam and Thailand as Market Leaders in the ASEAN Region - Ahmad Mikhail Samudra Usman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of electric vehicles (EVs) in the ASEAN region has demonstrated significant momentum, particularly in Vietnam and Thailand as key players in the green vehicle industry. This study aims to analyze the competitive advantages of the EV industry in Vietnam and Thailand through a comparative case study of VinFast and BYD, employing the differentiators perspective of Hambrick’s Diamond Strategy combined with SWOT analysis. The research adopts a post-positivist qualitative approach based on document analysis and literature review. The findings reveal that the market success of VinFast and BYD is strongly influenced by government policy support, effective product configuration, strong brand image, product reliability, and consistent differentiation strategies. VinFast’s advantages lie in its national brand identity, domestic market dominance, and cost efficiency, while BYD in Thailand excels through vertical integration, reliable supply chains, and proactive EV policies. The study offers strategic insights for Indonesia in accelerating the development of its EV and battery industry within the ASEAN renewable energy transition framework.